The Relationship Between Independent Commissioners, Corporate Social Responsibility, Leverage & Cash Flow Operations on Earnings Persistence with as Moderator Factor Audit Quality: Metod Scoping Riview - Ediyanto, Trijoko; Suratno, Suratno (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Based onhe twenty-three previous studies. There are some possibilities for futher research to explore some other alternative factor for antencedent and consequent factors on earning persistence. There are various sectors of industry as observation subject to be explored more in-dept. There are many possibilities to be explored about the earnings persistence